Money banking and international trade - Seth, M. L. (Agra, 1992)
Money, Banking, International Trade and Public Finance" is a text-book which has been especially planned to cater to the requirements of graduate, honours and post-graduate students in monetary theory at the university level. The book not only fully covers the prescribed courses of study but also presents the essentials of monetary theory in a compact, coherent, lucid and easily intelli gible manner. The courses of study prescribed by the Public Service Commis sion for the State and Central Services have also been borne in mind while writing the present volume. An attempt has been made to meet the requirements of candidates appearing for various professional examinations like Chartered Accountancy and Indian Institute of Bankers. The author feels that the present volume, as it stands now, leaves out nothing of importance which may be expec ted of graduate or post-graduate students in monetary theory.
Keywords: Money